Successful treatment with lenvatinib in a patient with thymic carcinoma presenting with cardiac tamponade: a case report and review of literature. Issue 8 (10th August 2022) - Nakashima, Koki; Azuma, Takayuki; Ohta, Rina; Fujii, Yuya; Sato, Masayuki; Igarashi, Kazunari; Kadowaki, Maiko; Umeda, Yukihiro; Waseda, Yuko; Anzai, Masaki; Kobayashi, Motohiro; Ishizuka, Tamotsu
Abstract : Thymic carcinoma (TC) presenting with cardiac tamponade has a poor prognosis because of the difficulty in controlling malignant pericardial effusion using conventional chemotherapy. Lenvatinib, a multitargeted kinase inhibitor of vascular endothelial growth factor receptor and other kinases, has recently been proven effective against TC. As the inhibition of vascular endothelial growth factor signaling is effective in malignant pericardial effusion, lenvatinib may also be effective in TC presenting with cardiac tamponade. However, no reports have shown that lenvatinib is effective in such cases. Herein, we present a case of successful treatment with lenvatinib in a patient with TC presenting with cardiac tamponade. The present case suggests that lenvatinib should be considered an effective treatment option for such cases.